Performance of Point-of-Care Testing Compared with the Standard Laboratory Diagnostic Test in the Measurement of HbA1c in Indonesian Diabetic and Nondiabetic Subjects - Afiat Berbudi; Nofri Rahmadika; Adi Imam Tjahjadi; Rovina Ruslami (Journal of Diabetes Research)
Objective. This study is aimed at investigating if point-of-care testing for HbA1c (POCT-HbA1c) using the HemoCue® HbA1c 501 system could be an alternative method for diabetes screening and monitoring to replace the HbA1c measurement in a standard diagnostic laboratory. Design. This was a cross-sectional study to assess the agreement between POCT and a standard laboratory measurement method for determining the level of HbA1c. Setting and Participants. In total, 108 participants were recruited to participate in this study, consisting of 61 diabetics and 47 nondiabetics. The diabetic group comprised 37 females and 24 males, diagnosed with type 2 diabetes mellitus (DM) and undergoing diabetes treatment at several community health care centres in Bandung, West Java. The nondiabetic group consisted of 15 female and 32 male patients of several community health care centres and healthy volunteers. Sample Collection and Analysis. A venous blood sample was taken for routine HbA1c analysis by the diagnostic laboratory method. For the POCT-HbA1c, a blood sample was taken from the fingertip at the same time and analysed with the HemoCue® HbA1c 501 system. Outcome Measures. The HbA1c results of both methods were compared and analysed with a Bland-Altman agreement plot. The sensitivity and specificity of the POCT-HbA1c data were also compared with those of the standard diagnostic results. Results. Based on the Bland-Altman plot, the HbA1c level for 100 out of 108 (92.59%) subjects analysed by the POCT-HbA1c was within the range of the 95% limit of agreement. Compared with the standard diagnostic assay, the sensitivity of the POCT-HbA1c was 97.83% and its specificity was 77.42%. Conclusions. The high sensitivity and accuracy of POCT-HbA1c indicate that it is a potential method for diabetes screening and monitoring to replace the routine diagnostic laboratory HbA1c measurement, especially when a rapid result is required.